New Lipaphis species (Hemiptera, Aphididae, Macrosiphini) from central Türkiye living on Sisymbrium sp. (Brassicaceae) - Özdemýr, Işil (Zootaxa, 2022)
Lipaphis (Lipaphis) erdemi sp. nov. is described from apterous and alatae viviparous females collected in Central Anatolia (Türkiye) on Sisymbrium sp. (Brassicaceae). The new species is markedly different from the other species of the subgenus Lipaphis by having secondary rhinaria on the antennal segments III, IV and frequently V in apterous viviparous females, and always having secondary rhinaria on the antennal segments III, IV and V in alate viviparae. Other features that allow to separate the new species from the other species of the subgenus are presented. The new species is morphologically most similar to L. erysimi and L. pseudobrassicae. An identification key based on apterous viviparous females of the genus Lipaphis known from Türkiye is provided.